Consensus on graft-versus-host disease - Vaneuza Araújo Moreira Funke; João Victor Piccolo Feliciano; Giancarlo Fatobene; Maria Cláudia Rodrigues Moreira; Antonio Vaz de Macedo; Rita de Cássia Barbosa da Silva Tavares; Marcia de Matos Silva; Marcos Paulo Colella; Morgani Rodrigues; Luis Fernando da Silva Bouzas; Afonso Celso Vigorito (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Graft-versus-host disease (GvHD) remains the mainly cause of late non-relapse mortality following allogeneic hematopoietic cell transplantation. Advancements in novel immunosuppressive therapies and prophylactic regimens necessitate an update to current clinical guidance. This consensus provides updated evidence-based recommendations for GVHD prophylaxis, alongside the treatment of acute and chronic disease.